ANALISIS KETIMPANGAN KEMANDIRIAN KEUANGAN DAERAH MENGGUNAKAN INDEKS WILLIAMSON ANTARKOTA DI SUMATERA BARAT - Tilawatil Ciseta Yoda; Rina Febriani (Bilancia : Jurnal Ilmiah Akuntansi, 2019)
Regional independence reflects the level of community participation in regional development, the more independent an area is, the higher the community participation in paying local taxes and fees which are the main components of Local Own-Source Revenue (LOSR). This study aims to evaluate and describe the level of inequality of regional financial independence using the Williamson Index between Cities in West Sumatra for the period 2014-2017. The method is using the analysis of the ratio of regional financial independence by looking at the comparison of the realization of LOSR to central government transfers, provincial transfers, and regional loans in 2014-2017, then the results were analyzed using the Willliamson Index to see the disparity of regional financial independence between Cities in West Sumatra. The result showed that The ratio of regional financial independence between cities in West Sumatra is categorized as Low with an average of 27.79%. Based on the Williamson Index, inter-city financial independence in West Sumatra has not been evenly distributed with the Inequal category. Kemandirian daerah menggambarkan tingkat partisipasi masyarakat dalam pembangunan daerah, semakin mandiri suatu daerah, semakin tinggi partisipasi masyarakat dalam membayar pajak dan retribusi daerah yang merupakan komponen utama PAD. Penelitian ini bertujuan untuk mengevaluasi, menggambarkan dan memetakan tingkat ketimpangan kemampuan kemandirian keuangan daerah menggunakan Indeks Williamson antar Kota di Sumatera Barat periode 2014-2017. Metode analisis data dengan menggunakan analisis rasio kemandirian keuangan dengan melihat perbandingan realisasi PAD dengan transfer pemerintah pusat, transfer provinsi, dan pinjaman daerah pada tahun 2014-2017, kemudian dari hasil rasio kemandirian keuangan dilakukan analisis menggunakan Indeks Willliamson untuk melihat ketimpangan kemampuan kemandirian keuangan daerah antar Kota di Sumatera Barat. Hasil Penelitian menunjukkanRasio kemandirian keuangan daerah antar Kota di Sumatera Barat dikategorikan Rendah dengan rata-rata 27,79%. Analisis menggunakan indeks Williamson di ketahui bahwa kemampuan kemandirian keuangan daerah antar Kota di Sumatera Barat belum merata atau berkategori Merata Moderat.